Roll on Aromaterapy Formula Activity Test Essential Oil Syzygium aromaticum L. - Ariyanti Ariyanti; Eni Masruriati; Mazikhatul Azka; Arini Asna Hidayah (GLOBAL HEALTH SCIENCE GROUP, 2020)
Syzygium aromaticum L. is a plant that contains essential oils. The essential oil of the clove plant is produced from the distillation of Syzygium aromaticum L.s, stalks, and leaves. The components of Syzygium aromaticum L. content are eugenol, eugenol acetate and cariophylene. The specifications of each part of the essential oil of Syzygium aromaticum L. (21.3%), eugenol (78-95%) using the Soxhlet method were about 47.57%. The purpose of this study was to determine the activity and effectiveness of the roll on formulation of Syzygium aromaticum L. essential oil. This study was experimental with the experimental design used was the posttest only controlled group. The research object was divided into two groups of treatment and control. The results showed that the roll on formulation of Syzygium aromaticum L. essential oil had a calming effect on mice. The most effective roll on formulation of Syzygium aromaticum L. essential oil is 7% concentration.